Impact of poor management in construction - Hazwani, Harif (2012)
Construction industry cannot run well without a good management team. Construction projects involve many parties namely the contractors, consultants, clients, suppliers, subcontractors and so forth. So, without a proper management, it is chaos. The negligence about management not only gives adverse impact to the company but also to clients and every party involved. The poor management problem in construction industry is a common phenomenon happen. Therefore, systematic management is important for the implementation of construction projects so that it will be well executed. This study is conducted to analyses the impact of poor management to the construction, to identify the causes and effects as well as to recommend on solutions to the problem. The study involved literature review as the foundation for information getting from books, journal, magazine and others. Questionnaire forms were being distributed randomly to get feedback from construction organizations as the primary data. The analysis is carried out using average index method. The main causes of poor management are weak and ineffective project manager, lack of responsibility and poor organization while the main effects of poor management are the risk to project, increase the construction cost and delay work.